Hypertension associated with increased renin concentrations in nephroblastoma. - Khan, A B (1991)
An infant with severe hypertension who had a nephroblastoma which was secreting active renin is described. Nephroblastoma must be included in the differential diagnosis of hypertension associated with increased renin concentrations, even in the absence of an abdominal mass.